2021
DOI: 10.1075/eww.20007.gol
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in British English voice quality

Abstract: This study considers regional variation of voice quality in two varieties of British English – Southern Standard British English and West Yorkshire English. A comparison of voice quality profiles for three closely related but not identical northern varieties within West Yorkshire is also considered. Our findings do not contradict the small subset of previous research which explored regional and/or social variation in voice quality in British English insofar as regionality may play a small role in a speaker’s v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Gold, E. Et al. Conducted a comparative study on the regional differences in the quality of speech sounds in Southern Standard British English and West Yorkshire English and concluded that the factors that produce the situation are superior to the inherent characteristics of the speaker's voice [18]. Jafar, A.…”
Section: Introductionmentioning
confidence: 99%
“…Gold, E. Et al. Conducted a comparative study on the regional differences in the quality of speech sounds in Southern Standard British English and West Yorkshire English and concluded that the factors that produce the situation are superior to the inherent characteristics of the speaker's voice [18]. Jafar, A.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, from the point of view of national music, the opera elements can better adapt to the cultural needs of the people of China. The people can recognize opera teaching integrated into vocal singing teaching (Gold et al, 2021). On the one hand, national vocal music can increase the pressure of performance while retaining the traditional elements of opera.…”
Section: Introductionmentioning
confidence: 99%